Internationalization and Family Firms: The Influence of Family Involvement on Exports - Eneko Urkiola; Alayo, Mikel (European Journal of Family Business, 2022)
Family firms show specific behavior in their internationalization because of the affective ties derived from the family’s influence in the business. The desire to achieve business and family objectives determines the strategic decision making of family members in governance and management, affecting the internationalization strategy. This research intends to determine the factors related to family influence in the internationalization of family firms. Thus, using a sample of 254 Spanish small- and medium-sized family firms, we analyze how family-related factors affect exports. The results confirm that family ownership and the generation in charge of the firm have positive effects on the export intensity of family firms. However, the results are not conclusive when assessing the relationship between family involvement in the board of directors and exports.